Optimization of biomass production of a mutant of Yarrowia lipolytica with an increased lipase activity using raw glycerol - Galvagno, Miguel Angel (2011)
Fil: Kronberg, María Florencia. Universidad de Buenos Aires. Facultad de Agronomía. Cátedra de Microbiología. Buenos Aires, Argentina.